Ergonomics Review : Identify Discomfort Seating Posture Among Elderly Taxi Drivers at Malaysia Perspective. - Majid, Ahmad Zuhairi Abdul; Yusoff, Irwan Syah Md; Tamrin, Shamsul Bahri Mohd (2017)
World Health Organization (WHO) describes people aged above 60 years old fall under a category of elderly.The alternative profession could involve with this community is to be taxi drivers.Therefore, numerous factors should take part to ensure the eldery taxi drivers could serve their best performance and in good health condition.